Effect of Transverse Base Width Restraint on the Cracking Behavior of Massive Concrete (Journal of Engineering, 2012)
The effect of considering the third dimension in mass concrete members on its cracking behavior is investigated in this study. The investigation includes thermal and structural analyses of mass concrete structures. From thermal analysis, the actual temperature distribution throughout the mass concrete body was obtained due to the generation of heat as a result of cement hydration in addition to the ambient circumstances. This was performed via solving the differential equations of heat conduction and convection using the finite element method. The finite element method was also implemented in the structural analysis adopting the concept of initial strain problem. Drying shrinkage volume changes were calculated using the procedure suggested by ACI Committee 209 and inverted to equivalent temperature differences to be added algebraically to the temperature differences obtained from thermal analysis. Willam-Warnke model with five strength parameters is used in modeling of concrete material in which cracking and crushing behavior of concrete can be included. The ANSYS program was employed in a modified manner to perform the above analyses. A thick concrete slab of 1.5m in thickness and 10m in length was analyzed for different widths 2, 4, 8, and 10m to produce different aspect ratios (B/L) of 0.2, 0.4, 0.8, and 1.0 respectively. The results of the analyses show an increase in cracking tendency of mass concrete member as the aspect ratio of the same member is increased due to the effect of transverse base restraint. Accordingly, such effect cannot be ignored in the analysis of base restrained mass concrete structures subjected to temperature and drying shrinkage volume changes.